A 32-Year-Old Woman (G2P1A0) with Partial HELLP Syndrome and Severe Preeclampsia in a Term Pregnancy - Arwin, Leonardo; Sari, Ratna Dewi Puspita (Medula, 2024)
Preeclampsia and HELLP syndrome are cases of obstetric emergencies that are still serious problems and have a high level of complexity. Preeclampsia is characterized by hypertension and proteinuria after 20 weeks of gestation, while HELLP syndrome is characterized by hemolysis, elevated liver enzymes, and thrombocytopenia. A 32 year old woman, term pregnant, G2P1A0, presented with a history of hypertension since pregnancy. The results of the physical examination, blood pressure was 165/120 mmHg, laboratory results showed that platelets were 150,000/µL, LDH 731 U/L, SGOT/SGPT 84/46 U/L and urine excretion showed proteinuria 500. The importance of knowing the risk factors for preeclampsia include the mother's age at the time. pregnant for more than 35 years, obesity, history of preeclampsia in a previous pregnancy, multiple pregnancies, and a history of certain diseases such as chronic hypertension, diabetes, kidney disease or degenerative diseases such as rheumatoid arthritis or lupus. Regular antenatal examinations and recognizing signs of preeclampsia as early as possible can prevent severe preeclampsia and its complications. Management of these patients includes stabilization, fluid management, preventing eclampsia, administering antihypertensive drugs and corticosteroids. Appropriate management in this case can prevent further complications and reduce maternal mortality. Diagnosis is based on anamnesis, physical examination and supporting support in patients given medical therapy in accordance with the theory and termination of pregnancy by caesarean section.